Bandwidth Extension of a Printed Square Monopole Antenna Loaded with Periodic Parallel-Plate Lines - Linglong Meng; Weimin Wang; Ming Su; Jinchun Gao; Yuanan Liu (International Journal of Antennas and Propagation)
A novel wideband monopole antenna employing periodically loaded parallel-plate lines is presented in this paper. The proposed antenna consists of a main square patch, a rectangular ground plane, and a periodical structure which is printed on both sides of substrate. A strong electromagnetic coupling technique is used to design the element that enhances impedance bandwidth and decreases the side-lobe level throughout the effective bandwidth. The antenna achieves a wide impedance bandwidth of about 61.1% or ranging from 2.16 to 4.06 GHz, an omnidirectional far-field pattern, and a peak radiation gain of 2.37 dBi. Finally, the proposed antenna is analyzed and measured. The measured results show satisfactory performance and good agreement with the simulated results.